2x+4=-5x+1

Simple and best practice solution for 2x+4=-5x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+4=-5x+1 equation:


Simplifying
2x + 4 = -5x + 1

Reorder the terms:
4 + 2x = -5x + 1

Reorder the terms:
4 + 2x = 1 + -5x

Solving
4 + 2x = 1 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
4 + 2x + 5x = 1 + -5x + 5x

Combine like terms: 2x + 5x = 7x
4 + 7x = 1 + -5x + 5x

Combine like terms: -5x + 5x = 0
4 + 7x = 1 + 0
4 + 7x = 1

Add '-4' to each side of the equation.
4 + -4 + 7x = 1 + -4

Combine like terms: 4 + -4 = 0
0 + 7x = 1 + -4
7x = 1 + -4

Combine like terms: 1 + -4 = -3
7x = -3

Divide each side by '7'.
x = -0.4285714286

Simplifying
x = -0.4285714286

See similar equations:

| 49n^2-81=0 | | 100=(x+2)+(x/2) | | -28=92+10x | | 100=x+2+x/2 | | 2(2w+12)=68 | | 4x-2(-1x-11)=64 | | 25a^2-80a+64=0 | | Z^2+8=4 | | a+(37+a)+(2a-40)=433 | | s-32=-29 | | 2x+8=352 | | (x)(x+1)(x+2)=36 | | 8x-(5x+4)=7+(2x-3) | | -5x+4(-3+3)=-192 | | x^2*y-3*x*y=0 | | 5(2a+4)=6a-4 | | 1.2m=.6 | | (x^2-5x-3)(x^2-5x-5)=3 | | -x+6x-9=0 | | 2y=-10x+4 | | -7=9x+16-10 | | 2(x+p)=3(6p-x) | | 9k-3k=30 | | 3y+4=y+18 | | -44-1x=28-4x | | x-7.1=-6.2 | | -(3y+1)-(-2y-7)=2 | | 96-2x=43x+16 | | 7(7x-3)+10x= | | 2x+80=158 | | 5p-3=32 | | 3x=3x+2 |

Equations solver categories